2013
DOI: 10.5455/2319-2003.ijbcp20130609
|View full text |Cite
|
Sign up to set email alerts
|

Study of prescribing pattern of antimicrobial agents in indoor patients of a tertiary care hospital

Abstract: Background: To evaluate prescribing pattern of antimicrobial agents in indoor patients of medicine and surgery department of SBH Government Medical College, Dhule. Methods: This was a retrospective cross sectional study carried over a period of 3 months. The patients who were admitted and received antimicrobial therapy in department of Medicine and Surgery were randomly selected and included in the study. The case record sheet and drug chart were obtained from Medical Record Section of the Hospital. The data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 2 publications
5
9
0
Order By: Relevance
“…In this study, the average number of antimicrobials prescribed in surgery department was 3 per patients. This is similar to that reported by Deshmukh, prescribing pattern of antimicrobial agents in indoor patients of SRTR Government Medical College, Maharashtra, which was 3.02 [12]. Another study conducted in Dr. B.R.…”
Section: Resultssupporting
confidence: 76%
“…In this study, the average number of antimicrobials prescribed in surgery department was 3 per patients. This is similar to that reported by Deshmukh, prescribing pattern of antimicrobial agents in indoor patients of SRTR Government Medical College, Maharashtra, which was 3.02 [12]. Another study conducted in Dr. B.R.…”
Section: Resultssupporting
confidence: 76%
“…This report is somewhat similar to reported by Deshmukh vs et al 27 was 66.2%. A study carried out by Pavani V et al, showed that 80% of patients received antimicrobial agents' appropriately 28 .…”
Section: Discussionsupporting
confidence: 78%
“…19 But result of present study was in approximate correspond to observation by Bharti Mahajan et al which had 3.36 AMA per prescription. 20 3.02 is the average number of AMA per prescription in study of Deshmukh VS et al 8 Most of the prescriptions had injectable antibiotic preferably as cases were from indoor setting. Majority of antibiotic were prescribed from National List of Essential Medicine, India and in WHO Model List of Essential Medicines (17 th edition).…”
Section: Discussionmentioning
confidence: 99%
“…The fear of physician whether he is missing any occult infection also makes him to use antibiotic umbrella for protecting him and his patient. 8 In order to get breakthrough from the irrational pattern of prescribing behaviour of antibiotic this study is done.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation